Catalytic Deoxygenative Cyclopropanation of 1,2-Dicarbonyl or Monocarbonyl Compounds via Molybdenum Catalysis - Wang, Jia-Le; Zhuo, Chun-Xiang (Synlett, 2021)
The cyclopropanation of alkenes through the transition-metal-catalyzed decomposition of diazo compounds is a powerful and straightforward strategy to produce cyclopropanes. Nevertheless, the appeal of further application of this strategy is tempered by the potentially explosive nature of the diazo substrates. Therefore, it is highly desirable to develop sustainable and operationally safe surrogates for diazo compounds. In this Synpacts article, we discuss recent advances on the cyclopropane syntheses through the catalytic cyclopropanation of alkenes and metal carbenes generated in situ from nondiazo precursors as well as highlight our recent progress on the unprecedented molybdenum-catalyzed deoxygenative cyclopropanation reaction of 1,2-dicarbonyl or monocarbonyl compounds.
Keywords: cyclopropane syntheses; diazo surrogates; transition-metal carbene; molybdenum catalysis; deoxygenative cyclopropanation